Gestational Diabetes Mellitus Subtypes Classified by Oral Glucose Tolerance Test and Maternal and Perinatal Outcomes: Results of a Mexican Multicenter Prospective Cohort Study “Cuido Mi Embarazo” - Ortega-Montiel J; Martinez-Juarez LA; Montoya A; Morales-Juárez L; Gallardo-Rincón H; Galicia-Hernández V; Garcia-Cerde R; Ríos-Blancas MJ; Álvarez-Hernández DA; Lomelin-Gascon J; Martínez-Silva G; Illescas-Correa LM; et al. (Diabetes, Metabolic Syndrome and Obesity, 2024)
Janinne Ortega-Montiel,1 Luis A Martinez-Juarez,1,2 Alejandra Montoya,1 Linda Morales-Juárez,3 Héctor Gallardo-Rincón,1,4 Victoria Galicia-Hernández,1 Rodrigo Garcia-Cerde,1 María Jesus Ríos-Blancas,1 Diego-Abelardo Álvarez-Hernández,1 Julieta Lomelin-Gascon,1 Gisela Martínez-Silva,1 Lucía M Illescas-Correa,5 Daniel A Diaz Martinez,6 Francisco Javier Magos Vázquez,6 Edwin Vargas Ávila,6 Ma Concepción Carmona-Ramos,7 Ricardo Mújica‐Rosales,1 Enrique Reyes-Muñoz,8 Roberto Tapia-Conyer9 1Carlos Slim Foundation, Mexico City, Mexico; 2Johns Hopkins Center for Humanitarian Health, Bloomberg School of Public Health, Baltimore, MD, USA; 3Institute for Obesity Research, Tecnológico de Monterrey, Mexico City, Mexico; 4Health Sciences University Center, University of Guadalajara, Guadalajara, Jalisco, Mexico; 5Maternal and Childhood Research Center (CIMIGEN), Mexico City, Mexico; 6Ministry of Health of the State of Guanajuato, Tamazuca, Guanajuato, Mexico; 7Ministry of Health of the State of Hidalgo, Pachuca, Hidalgo, Mexico; 8Coordinatión of Gynecological and Perinatal Endocrinology, National Institute of Perinatology Isidro Espinosa de los Reyes, Mexico City, Mexico; 9National Autonomous University of Mexico, School of Medicine, Mexico City, MexicoCorrespondence: Alejandra Montoya, Carlos Slim Foundation, Lago Zurich 245, Presa Falcon Building (Floor 20), Col. Ampliación Granada, Miguel, Hidalgo, Mexico City, 11529, Mexico, Tel +52 55 4976 0344, Email airainmr@fundacioncarlosslim.orgPurpose: This study explores the impact of gestational diabetes mellitus (GDM) subtypes classified by oral glucose tolerance test (OGTT) values on maternal and perinatal outcomes.Patients and Methods: This multicenter prospective cohort study (May 2019–December 2022) included participants from the Mexican multicenter cohort study Cuido mi Embarazo (CME). Women were classified into four groups per 75-g 2-h OGTT: 1) normal glucose tolerance (normal OGTT), 2) GDM-Sensitivity (isolated abnormal fasting or abnormal fasting in combination with 1-h or 2-h abnormal results), 3) GDM-Secretion (isolated abnormal values at 1-h or 2-h or their combination), and 4) GDM-Mixed (three abnormal values). Cesarean delivery, neonates large for gestational age (LGA), and pre-term birth rates were among the outcomes compared. Between-group comparisons were analyzed using either the t-test, chi-square test, or Fisher’s exact test.Results: Of 2,056 Mexican pregnant women in the CME cohort, 294 (14.3%) had GDM; 53.7%, 34.4%, and 11.9% were classified as GDM-Sensitivity, GDM-Secretion, and GDM-Mixed subtypes, respectively. Women with GDM were older (p = 0.0001) and more often multiparous (p = 0.119) vs without GDM. Cesarean delivery (63.3%; p = 0.02) and neonate LGA (10.7%; p = 0.078) were higher in the GDM-Mixed group than the overall GDM group (55.6% and 8.4%, respectively). Pre-term birth was more common in the GDM-Sensitivity group than in the overall GDM group (10.2% vs 8.5%, respectively; p=0.022). At 6 months postpartum, prediabetes was more frequent in the GDM-Sensitivity group than in the overall GDM group (31.6% vs 25.5%). Type 2 diabetes was more common in the GDM-Mixed group than in the overall GDM group (10.0% vs 3.3%).Conclusion: GDM subtypes effectively stratified maternal and perinatal risks. GDM-Mixed subtype increased the risk of cesarean delivery, LGA, and type 2 diabetes postpartum. GDM subtypes may help personalize clinical interventions and optimize maternal and perinatal outcomes.Keywords: Gestational Diabetes, GDM-Mixed, GDM-Secretion, GDM-Sensitivity, macrosomia, cesarean delivery, pre-term delivery